The differences in three-dimensional kinetics in lower limb joints of sprinters and novice runners during a start dash - Otsuka, M.; Yoshioka, S.; Kurihara, T.; Isaka, T. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to clarify the differences in the three-dimensional joint moments of lower limbs between sprinters and novice runners. A total of 12 male sprinters and 11 healthy male college students participated in a start-dash experiment. At pushing the front starting block, in hip joint, extension moment of sprinters was significantly greater than that of novices. On the other hands, in ankle joint, not only the plantarflexion moments but also the inversion moment of sprinters was significantly greater than those of novices. Moreover, the peak value of the plantarflexion moment was positively correlated with that of the inversion moment. These results suggest that the greater ankle flexion-extension moment is achieved by coordinating with the greater inversion moments when attempting to increase acceleration ability.